PENGARUH WARNA LAMPU YANG BERBEDA TERHADAP HASIL TANGKAPAN BAGAN TANCAP DI TELUK LEMBAR: The Effect of Different Light Colors on the catch of the step chart in the shett bay Lembar - Nursam, Lalu; Artiningrum, Novita Tri; Kalih, L.A.T.T.W. Sukmaring; Soraya, Indah (Al-Qalbu: Jurnal Pendidikan, Sosial dan Sains, 2023)
The aim of this research is to describe the influence of the color of the lights on the type and composition of fish caught in the Tancap Chart in Sheet Bay and to describe the influence of the color of the lights on the B/C Ratio of the Tancap Chart caught in the Sheet Bay. This research was carried out in Teluk Selamat Village, Labuan Tereng District. West Lombok Regency Sheet from June - July 2021. This research uses an experimental method with a Completely Randomized Design (CRD) consisting of four treatments and four replications each, the four treatments are step charts using white lights, treatment II using yellow light, and treatment III using blue light and treatment IV using red light. The results of the research showed that the tancap chart with the treatment using white lights caught the most, which means it had the most influence on the total weight of the catch, followed by yellow, blue and red lights, the fish composition in each treatment, the dominant fish caught was tamban fish. (Sardinella sp). The largest B/C Ratio results were obtained on the step chart with white then yellow, red and blue lights (B/C Ratio > 1) indicating that the business being carried out is profitable, meaning the business is worthy of development